LGBT sensitization amongst children with cerebral paresis (Training and Practice : Journal of Educational Sciences, 2018)
School as a secondary socialization area undeniably forms the children’s world view. Equality, antidiscrimination are accepted in theory, but they are not integrated into everyday practice completely. Until there is discrimination against ethnicity, genders, sexualities or disabled people in the media, there will be discrimination in the classrooms. I did my research in an under-examined area: the awareness and attitude towards LGBT people, amongst youngsters with cerebral paresis. I examined seven children’s attitude in a class in spontaneous situations and in guided conversations, before a sensitization training held by me and immediately after the training and in perspective of two months.